The hieronymite father Diego Cisneros, the forbidden books and the peruvian publication Mercurio Peruano - Campos y Fernández de Sevilla, Francisco Javier (2012)
Friar Diego Cisneros (1737-1812) was a Hieronymite monk at El Escorial and librarian at the Royal Spanish Library. In 1772 he went to Peru as auditor of the rents of some encomiendas granted by Philip IV of Spain to a monastery in payment for prayers, a system that the king himself had created, he was also in charge of the sale of liturgical books called Nuevo Rezado (New forms of prayer). For his broad cultural background and open mind he soon made contact with the intellectuals of Lima and became a member of the Society of True patriots which edited a magazine called Mercurio Peruano (Peruvian Mercury) which was an important cultural project is the last decade of the eighteenth century.